Influence of Compensation, Work Environment, Motivation, and Work Spirit on Employee Performance Botanical Garden Bedugul - Ekadharma Susila, Bagus Putu; Ariantini, Putu Oka (Akademi Komunitas MAPINDO, 2023)
Bedugul Botanical Garden is one of the tourism objects in Tabanan Regency which is packaged as anagrotourism for foreign and domestic tourists. This research aims to analyze the influence of compensation,work environment, motivation and work spirit on the performance of Botanical Garden Bedugul employees.Determining the number of research samples is based on the Slovin formula, so that the number of researchsamples can be determined as 77 employees from all Botanical Garden Bedugul employees totaling 326 people.The sampling technique uses the Cluster Random Sampling technique. Data collection methods use interviews,questionnaires and documentation. The analysis technique in the research uses multiple regression analysistechniques. The results of research using the t statistical test show that partially compensation, workenvironment, motivation and work spirit have a positive and significant effect on the performance of BotanicalGarden Bedugul employees. The magnitude of the influence of each independent variable on the performanceof Botanical Garden Bedugul employees is compensation of 18%, work environment of 8.7%, motivation of30.7% and work morale of 15.5%. Hypothesis testing using the F statistical test (ANOVA) shows thatsimultaneously compensation, work environment, motivation and work spirit have a positive and significanteffect on the performance of Botanical Garden Bedugul employees. The motivation variable has a moredominant influence on the performance of Botanical Garden Bedugul employees. The implication of thisresearch is one of the considerations in efforts to improve the performance of Botanical Garden Bedugulemployees which can be done by maintaining employee motivation and morale as well asimproving/improving the employee work environment.Keywords: Compensation, Work Environment, Motivation, Work Spirit, Employee Performance